Sprint acceleration mechanical outputs derived from position- or velocity-time data: a multi-system comparison study - Fornasier-Santos, C.; Arnould, A.; Jusseaume, J.; Millot, B.; Guilhem, G.; Couturier, A.; Samozino, P.; Slawinski, J.; Morin, J.-B. (Sensors, 2022)
To directly compare five commonly used on-field systems (motorized linear encoder, laser, radar, global positioning system, and timing gates) during sprint acceleration to (i) measure velocity-time data, (ii) compute the main associated force-velocity variables, and (iii) assess their respective inter-trial reliability. Eighteen participants performed three 40 m sprints, during which five systems were used to simultaneously and separately record the body center of the mass horizontal position or velocity over time. Horizontal force-velocity mechanical outputs for the two best trials were computed following an inverse dynamic model and based on an exponential fitting of the position- or velocity-time data. Between the five systems, the maximal running velocity was close (7.99 to 8.04 m.s-1), while the time constant showed larger differences (1.18 to 1.29 s). Concurrent validity results overall showed a relative systematic error of 0.86 to 2.28% for maximum and theoretically maximal velocity variables and 4.78 to 12.9% for early acceleration variables. The inter-trial reliability showed low coefficients of variation (all <5.74%), and was very close between all of the systems. All of the systems tested here can be considered relevant to measure the maximal velocity and compute the force-velocity mechanical outputs. Practitioners are advised to interpret the data obtained with either of these systems in light of these results.